2014
DOI: 10.12681/mms.812
|View full text |Cite
|
Sign up to set email alerts
|

Biology and population dynamics of by-catch fish species of the bottom trawl fishery in the western Mediterranean

Abstract: The teleosts Chelidonichthys cuculus, Trigloporus lastoviza, Serranus cabrilla and Trachinus draco, are important by-catch species, in terms of landed biomass and commercial value, from the continental shelf bottom trawl fishery off the Balearic Islands (western Mediterranean). The main biological parameters of these species were calculated from monthly biological samplings, and were used along with three-year pseudo-cohorts (2008)(2009)(2010) obtained from monitoring on-board of the bottom trawl fleet, to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Owing to its high overexploitation, stronger measures should be enforced for hake and even a recovery plan might be considered. In addition, the ecosystem-based fisheries management must integrate not only the main target stocks, but also relevant by-catch species (Ordines et al, 2014) and take into account the conservation of the habitats present on the fishing grounds .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its high overexploitation, stronger measures should be enforced for hake and even a recovery plan might be considered. In addition, the ecosystem-based fisheries management must integrate not only the main target stocks, but also relevant by-catch species (Ordines et al, 2014) and take into account the conservation of the habitats present on the fishing grounds .…”
Section: Discussionmentioning
confidence: 99%
“…L. cavillone and C. cuculus off the western coasts of Italy appear more abundant on the detrital bottoms over the continental shelf break (Serena et al 1990, Colloca et al 1997, Damalas et al 2010. L. diuzeidei was found to be more common on the detrital and muddy bottoms of the shallow part of the upper slope (Voliani et al 2000), while on the coastal shelf, C. lucerna was concentrated on the coastal and detrital sandy bottoms and C. lastoviza on the coastal detrital sediments (Serena et al 1990, Ordines et al 2014. In this study, we found that the areas showing the highest gurnard abundances are those characterized by the prevalence or the wide extension of detrital bottoms, such as Malta, the Balearic Islands, the Greek GSAs and the south of Sicily, the latter characterized by wide offshore banks (Di Lorenzo et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the largest-sized species such as C. lucerna, T. lyra, E. gurnardus, C. cuculus and C. lastoviza are a valuable by-catch of demersal fisheries of many Mediterranean sectors (Ordines et al 2014). Although the impact of fishing on the gurnard populations has rarely been examined, Ordines et al (2014) pointed out that some commercially important gurnards, such as C. lastoviza and C. cuculus, have also been affected by the overall overexploitation of commercial stocks in the Mediterranean (Colloca et al 2013, Cardinale et al 2017. As a result, their levels of overexploitation are similar to, or even higher than, those detected for some of the most important target species such as hake and red mullet (Ordines et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Mediterranean, both the scientific community and the European Commission have recognized an alarming situation (Vasilakopoulos, Maravelias, & Tserpes, ), as most of the currently assessed nekto‐benthic stocks are overexploited (Colloca et al, ; European Environmental Agency, ; Tsikliras, Dinouli, Tsiros, & Tsalkou, ). In addition, many of the bottom‐trawling fisheries operating in this region are multispecific and, since gear selectivity is typically low (Lleonart & Maynou, ), a great deal of the effort is exerted on non‐target species (Moranta, Massutí, & Morales‐Nin, ; Ordines et al, ; Sánchez, Demestre, & Martí, ). The Mediterranean is a biodiversity hotspot and a conservation area of global priority (e.g.…”
Section: Introductionmentioning
confidence: 99%